Local Transcriptional Control of YUCCA Regulates Auxin Promoted Root-Growth Inhibition in Response to Aluminium Stress in Arabidopsis - Liu, Guangchao; Gao, Shan; Tian, Huiyu; Wu, Wenwen; Robert, Hélène S; Ding, Zhaojun (PLoS genetics, 2016)
Auxin is necessary for the inhibition of root growth induced by aluminium (Al) stress, however the molecular mechanism controlling this is largely unknown. Here, we report that YUCCA (YUC), which encodes flavin monooxygenase-like proteins, regulates local auxin biosynthesis in the root apex transition zone (TZ) in response to Al stress. Al stress up-regulates YUC3/5/7/8/9 in the root-apex TZ, which we show results in the accumulation of auxin in the root-apex TZ and root-growth inhibition during the Al stress response. These Al-dependent changes in the regulation of YUCs in the root-apex TZ and YUC-regulated root growth inhibition are dependent on ethylene signalling. Increasing or disruption of ethylene signalling caused either enhanced or reduced up-regulation, respectively, of YUCs in root-apex TZ in response to Al stress. In addition, ethylene enhanced root growth inhibition under Al stress was strongly alleviated in yuc mutants or by co-treatment with yucasin, an inhibitor of YUC activity, suggesting a downstream role of YUCs in this process. Moreover, ethylene-insensitive 3 (EIN3) is involved into the direct regulation of YUC9 transcription in this process. Furthermore, we demonstrated that PHYTOCHROME INTERACTING FACTOR4 (PIF4) functions as a transcriptional activator for YUC5/8/9. PIF4 promotes Al-inhibited primary root growth by regulating the local expression of YUCs and auxin signal in the root-apex TZ. The Al-induced expression of PIF4 in root TZ acts downstream of ethylene signalling. Taken together, our results highlight a regulatory cascade for YUCs-regulated local auxin biosynthesis in the root-apex TZ mediating root growth inhibition in response to Al stress.
Keywords: Arabidopsis Proteins; Arabidopsis; Basic Helix-Loop-Helix Transcription Factors; transkripční faktory bHLH; Signal Transduction; Aluminum; Transcription Factors; Oxygenases; transkripční faktory; aktivace transkripce; kyseliny indoloctové; Nuclear Proteins; jaderné proteiny; oxygenasy; signální transdukce; fyziologický stres; ethyleny; Gene Expression Regulation, Plant; Transcriptional Activation; Indoleacetic Acids; Plant Roots; hliník; kořeny rostlin; regulace genové exprese u rostlin; Ethylenes; Stress, Physiological; proteiny huseníčku